A new anti-austerity agent, 4′-O-methylgrynullarin from Derris scandens induces PANC-1 human pancreatic cancer cell death under nutrition starvation via inhibition of Akt/mTOR pathway. (15th May 2021) - Sun, Sijia; Dibwe, Dya Fita; Kim, Min Jo; Omar, Ashraf M.; Phan, Nguyen Duy; Fujino, Haruka; Pongterdsak, Nusrin; Chaithatwatthana, Kritsaya; Phrutivorapongkul, Ampai; Awale, Suresh
Graphical abstract: Abstract: An ethanolic extract of Derris scandens flowers showed potent preferential cytotoxicity against PANC-1 human pancreatic cancer cells under nutrient-deprived condition, with a PC50 value of 0.7 μg/mL. Phytochemical investigation of this active extract led to the isolation of four prenylated isoflavones (1 –4 ) including a new compound named 4′- O -methylgrynullarin (1 ). The structure elucidation of the new compound was achieved by HRFABMS and NMR spectroscopic analysis. The isolated compounds exhibited potent anti-austerity activity against four different human pancreatic cancer cell lines under nutrient-deprived conditions. The new compound 4′- O -methylgrynullarin (1 ) was also found to inhibit PANC-1 cell migration and colony formation under nutrient-rich condition. Mechanistically, compound 1 inhibited key survival proteins in the Akt/mTOR signaling pathway. Therefore, 4′- O -methylgrynullarin (1 ) can be considered as a potential lead compound for the anticancer drug development based on the anti-austerity strategy.